(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2024)
The bambara bean (Vigna subterranea (L.) Verdc.) is native to the African continent, being considered rustic, tolerant to water stress, high temperatures, and soils with low fertility. In view of climate change, it’s a strategic crop having a short cycle and a fast economic return. The practice of mounding is considered essential for crops that have parts of economic interest below the soil surface promoting better plant development, protection against solar radiation and weed control. The objective of this work was to evaluate the phytotechnical aspects of bambara bean under different periods of mounding. The methodology used was a randomized block design with three treatments and six repetitions submitted to the Tukey test at 5% probability. The treatments were no mounding (SA), mounding 60 days after planting (A60AP), and mounding 90 days after planting (A90AP). The parameters analyzed were mass of 100 seeds (M100S), number of seeds per plot (NSP), productivity in kg/ha (PR), and number of seeds per kilo (NSQ). The results pointed out that mounding brings positive results for M100S and PR for A60AP. A90AP and SA had reductions in M100S and increase in NSQ when compared to A60AP. The variable NSP was not influenced by any of the treatments. Thereby, A60AP lead to a greater increase in productivity and quality for bambara groundnut in region of MG, Brazil.